Феномен мелодии Мирослава Скорика из фильма «Высокий перевал» - Морева, Е.А. (Культура народов Причерноморья, 2014)
Статья посвящена уникальному явлению в контексте взаимодействия
кинематографического и музыкального искусств – знаменитой Мелодии М. Скорика из фильма
Владимира Денисенко «Высокий перевал». Музыкальная доминанта в этом особом синтезе привела к
особенному результату, который проявился в дальнейшем отдельном существовании Мелодии как
полноценного и самодостаточного произведения. Однако ее содержание, первоначально связанное с
трагическим контекстом фильма, отлично от ее семантики в концертных исполнениях, поэтому есть
необходимость в анализе ее образно-интонационной природы. Стаття присвячена унікальному явищу в контексті взаємодії кінематографічного і
музичного мистецтв – знаменитій Мелодії М. Скорика з фільму Володимира Денисенка «Високий
перевал». Музична домінанта в цьому особливому синтезі призвела до особливого результату, який
проявився в подальшому окремому бутті Мелодії як повноцінного і самодостатнього твору. Однак її
зміст, пов'язаний з трагічним контекстом фільму, відрізняється від її семантики у концертних
виконаннях, тому є необхідність в аналізі її образно-інтонаційної природи. The article is devoted to the unique phenomenon in the context of the interaction of cinematic and
musical art – Famous Melodies by Skoryk from the film by Vladimir Denisenko «High Pass». Musical dominant
in this particular synthesis led to a feature of the results that emerged later on a separate existence as a fullfledged
melodies and self-contained work. However, its content is initially associated with the tragic context of
the film is different from its semantics in a concert performance, so there is a need to analyze its figurative
nature of intonation. The phenomenon of its popularity, in our opinion, is that it is easily remembered by
chanting the initial tone and a rhythmic pattern with his melodic variation, and, of course, in her beauty. It is
based on the same theme grains, which is being developed by a thematic variation and sequencing, keeping
himself intonation momentum throughout its length. This method of development is close endless melody
baroque type with the corresponding techniques of the Baroque monothematicism. Hidden national traits that
appear only in the time of the merger of the two themes of the film, is also one of the reasons for the popularity
of ringtones.